The NGF Point-Injection for Treatment of the Sound-Perceiving Nerve Deafness and Tinnitus in 68 Cases - 周枫 吴萍 王黎 王海涛 章少彬 林薏 钟慧 陈燕华 (Journal of traditional Chinese medicine, 2009)
Objective： To observe the therapeutic effects of the point-injection with nerve growth factor （NGF） for the sound-perceiving nerve deafness and tinnitus. Methods： The 140 cases in this series were randomly divided into a treatment group of 68 cases treated by NGF injection at the points of Yifeng （TE 17） and Wangu （GB 12）, and a control group of 72 cases orally taking Xibiling （西比灵） and adenosine triphosphate （ATP） and intramuscular injection with VB1 and VB12. Results： The total effective rate was 78.6% in the treatment group and 31.8% in the control group, with significant difference between the two groups （P〈0.05）. Conclusion： For treating nervous deafness and tinnitus, NGF point-injection may show good therapeutic effects, but inversely proportional to the illness course, age and the extent of hypoacusis.